Primary Hydatid Cyst of the Axillary Region: A Case Report - Mehrangiz Zangeneh; Mahmood Amerion; S. Davar Siadat; Mohsen Alijani (Case Reports in Medicine)
Introduction. Hydatid disease is a disease caused by the cestode Echinococcus. Echinococcus granulosus is the most common Echinococcus species affecting human. It may affect any organ and tissue in the body, most in the liver and lung. Disease is endemic in some regions of the world, and is common in Iran. Primary hydatid cyst of the axillary region is an unusual and rare localization of hydatid disease. So far, only sixteen cases have been published in the all medical literature. Case Report. Herein, we present a 33-year-old woman because of a mass in the axillary region of four months duration. Axillary ultrasonography showed a thick wall cystic lesion. No abnormality was found in mammographic examination of either breast, or in abdominal ultrasonography and chest X-ray. The mass was excised for pathological examination that showed a typical laminated membrane of hydatid cyst. Postoperative IgG- ELISA serology in this case was negative. Based on pathology an axillary hydatid cyst was diagnosed. Conclusion. Hydatid cyst should be considered in endemic areas in patients presenting with a soft tissue mass in the axillary region.